Multiple receptor sites in Achatina fulica ferussac neurons for a molluscan tetrapeptide amide (FMRF-AMDE) - Kim, Kah Hwi; Muhamad, M.A.; Cheah, Swee Hung; Raman, A. (Faculty of Medicine, University of Malaya, 1996)
The effects of Phe-Met-Arg-Phe-NH2 (FMRF-amide) and its analogue Phe-Leu-Arg-Phe-NH2 (FLRF-amide) on the nervous system were studied on thirtyfour identified neurons of the snail Achatina fulica Ferussac (locally known as "siput babi"). The results showed that FMRF-amide and FLRF-amide induced three different types of responses on the membrane potential of these neurons. First, FMRF-amide and FLRF-amide induced slow hyperpolarizing responses in TAN, d-LCDN, RAPN, d-LPeCN and V-RPLN. These responses remained unchanged in Cl--free, Ca2+ -free and 20% Na+ saline. The hyperpolarization was slightly reduced in 200% K+ and slightly enhanced in 50% K+ saline. Thus, the slow hyperpolarizing responses induced by FMRF-amide and FLRF-amide in the above neurons were K + -dependent. Second, FMRF-amide and FLRF-amide induced rapid and transient hyperpolarizing responses on RPeNLN, LPeNLN and TAN-2. The effect persisted in 200% K+, 20% Na+ and Ca2+ -free saline. However, in Cl--free saline, the effects were transient rapid depolarizing responses. This observation suggested that CI- was responsible for the hyperpolarizing responses. Third, FMRF-amide and FLRF-amide induced depolarizing responses in INN and this effect remained unchanged in Ca2+ -free saline. However, in 20% Na+ saline, the depolarizing responses were abolished. Thus, the involvement of Na+ was implicated in the observed depolarizing responses. The observed 3 different responses induced by FMRF-amide and FLRF-amide on Achatina fulica Ferussac neurons were comparable to their effects on the neurons of the gastropods Aplysia and Helix. Thus, FMRF-amide induced its multiple effects via multiple receptor sites, analogous to its action on Helix and Aplysia neurons